Development of Circular Motion E-Module Using Canva in Physics Subjects in High School - Aisyah Dewi; Lukman Hakim; Linda Lia (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
The purpose of this research is to develop circular motion e-modules using Canva in high school that are valid and practical and have a potential impact on learning outcomes. The research is product oriented with Rowntree. There are three phases in this research, namely planning, development, and evaluation. Evaluation uses Tessmer formative evaluation. The instruments used are walkthroughs, interviews, questionnaires, and tests. This study involved 37 students. The e-module product was declared valid by experts who obtained an average score based on the material aspect 3.67 very valid category, design aspect 3.67 very valid category, language aspect 3.67 very valid category, and media aspect 3.48 very valid category. The e-module product scored an average percentage of 90% in the very practical category at the one to one and 84% in the very practical category at the small group. The field test got an average pretest score of 64.42 in the good category and posttest 91.73 in the the n-gain of 0.74 students in the high category. Thus, the conclusion obtained is that the circular motion e-module product using the Canva is suitable for use in learning.